(untitled) (Nexo Revista Científica, 2021)
The article is devoted to the theoretical and legal analysis of information security systems in some countries of the Asian region. It is proposed to consider the information protection system as a set of interrelated elements and their interactions aimed at preventing and countering threats in the information sphere, as well as developing and improving the system itself. The system-structural approach allowed the author to highlight the following elements of the information security system: objects, subjects, scope, functions, conditions and directions of the system, principles and legal framework. The main trend in the field of information security of these countries is the strengthening of state regulation of their cyberspace. In particular, the legislation of these countries strictly regulates the rights, duties and responsibilities of the owners of information resources on the Internet, news aggregators, instant messengers and search engine operators.